A one-pot synthesis of a monolithic Cu2O/Cu catalyst for efficient ozone decomposition. Issue 67 (10th November 2020) - Rahimi, Mohammad Ghasem; Wang, Anqi; Ma, Guojun; Han, Ning; Chen, Yunfa
Abstract : Nowadays, it is necessary and challenging to prepare monolithic catalysts, which are ready for use, preventing the tedious and complicated integration procedure of the powder materials onto a porous substrate. Abstract : Nowadays, it is necessary and challenging to prepare monolithic catalysts, which are ready for use, preventing the tedious and complicated integration procedure of the powder materials onto a porous substrate. Herein, Cu2 O nanoparticles are successfully synthesized onto a porous Cu foam in one pot via the surface oxidation, coordination and precipitation reactions in a NH4 OH and HCl solution, and the optimum synthesis conditions are a NH3  : HCl ratio of 1 : 0.9, oxidation temperature of 80 °C and time of 18 h. The obtained Cu2 O/Cu catalyst (mostly <100 nm) shows a highly active O3 decomposition performance with >98% and >80% conversion efficiency in dry and 90% relative humidity air for >10 h at an O3 concentration of 20 ppm and a gas hourly space velocity of 12 500 h −1 . The high efficiency can be attributed to the porous Cu foam providing a large contact area, abundant crystal defects in the nanometer-sized Cu2 O materials serving as the active sites, and also to the Schottky barrier formed in the Cu2 O/Cu interface facilitating the electron transfer for O3 degradation. All these results show the potency of the easily fabricated monolithic Cu2 O/Cu catalyst for the highly efficient O3 contaminant removal.